THE EFFECT OF HUMAN CAPITAL AND SOCIAL CAPITAL ON PRODUCTIVITY OF COMPETITIVENESS - Hendayana, Yana; Riantani, Suskim; Eka Sumadhinata, Yelli; Dyahrini, Wien; Boga Kuswara, Galuh (International Journal of Psychosocial Rehabilitation, 2020)
This study analyzes the competitiveness of the creative industry subsector of the doll industry in West Java Province, which is influenced by human capital, social capital, and productivity, which have an effect on the competitiveness. The aim of this research is to know and analyze the effect of human capital and social capital, directly and through productivity, on competitiveness. This research used a quantitative approach as a survey method. The unit of analysis of this study is the SMEs (small and medium enterprises) Center of the Doll Industry Subsector Creative Industry in West Java Province, with entrepreneurs as the observation unit, with a population of 191 entrepreneurs and a sample of 128 entrepreneurs. Data obtained from the survey results through a questionnaire distributed to entrepreneurs. Data were processed using descriptive statistical analysis. Likewise, human capital, social capital, and productivity have significant and positive effects on competitiveness. These findings suggest that productivity can be an intervening variable for competitiveness. The effect of this research is expected to increase the competitiveness of the doll industry in Indonesia’s West Java Province.